Gatekeeping African studies: A preliminary insight on what do editorial boards indicate about the nature and structure of research brokerage - Mendonça, S.; Pereira, J.; Ferreira, M. E. (STI2016: 21st international conference on science and technology indicators: Book of proceedings, 2016)
Issues of inequality and distribution of different sorts constitute salient aspects in the agenda of development studies. As globalisation unfolds new indicators are needed in order to update the capacity identify, capture, and interpret its dynamics and asymmetries. Notwithstanding the many changes in the world’s socio-economic landscape, Africa, in particular, remains a marginal geographical and cognitive space. This research deals with a particular segment of the development studies “academic value chain”. Unlike much of the contemporary work on scientometrics, this paper does not primarily analyse publications or citations. Our data regards the composition and characteristics of editorial boards in the field under analysis.